The Eastern Christian Tradition in Modern Russian Thought and Beyond - Obolevitch, Teresa, (Contemporary Russian Philosophy ;, 2022)
In The Eastern Christian Tradition in Modern Russian Thought and Beyond, Teresa Obolevitch reflects on the ontology and anthropology of neo-patristic synthesis and its connection to Western philosophy, with a focus on the work of Georges Florovsky and Vladimir Lossky. The book also examines the concept of apophaticism in Russian philosophy: in neo-patristic synthesis and the thought of Semyon Frank and Lev Karsavin, as well as in epistemological and cosmological comparison with process theology. Additionally, Obolevitch's work undertakes a comparative analysis of the reception of Russian sophiology in the West, especially in the work of Thomas Merton, and also considers similarities between neo-patristic synthesis and Zen Buddhism in the thought of Merton and Sergey Horujy.